2023
DOI: 10.3390/jcdd10020062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Systematic Use of Intracardiac Ultrasound during Transseptal Catheterization in the Electrophysiology Laboratory

Abstract: Aims: To explore the impact of the use of intracardiac echocardiography (ICE) in the ablation of supraventricular arrhythmias requiring transseptal catheterization (TSC), whilst analyzing the reduction in periprocedural complications and complications specifically related to TSC. Methods: A retrospective multicenter study collecting data from consecutive atrial fibrillation (AF) and supraventricular ablation procedures that required TSC was performed in five Italian centers. Based on physician discretion, TSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The best example of a technique which significantly improved ablation procedures during everyday EP practice is ICE. It has been shown that ICE imaging improves EP lab workflow in terms of safety and efficacy and decreases periprocedural complications and duration of complex procedures 22–25 . In cases of idiopathic VA ablation, it was also valuable to be able to discern pouches in the interventricular septum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best example of a technique which significantly improved ablation procedures during everyday EP practice is ICE. It has been shown that ICE imaging improves EP lab workflow in terms of safety and efficacy and decreases periprocedural complications and duration of complex procedures 22–25 . In cases of idiopathic VA ablation, it was also valuable to be able to discern pouches in the interventricular septum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ICE imaging improves EP lab workflow in terms of safety and efficacy and decreases periprocedural complications and duration of complex procedures. [22][23][24][25] In cases of idiopathic VA ablation, it was also valuable to be able to discern pouches in the interventricular septum. Thanks to ICE imaging, steerable sheath retrograde access via femoral artery could be limited only to detailed mapping of LVOT/aortic cusps.…”
Section: Summitmentioning
confidence: 99%
“…Bottoni et al . [ 11 ] conducted a large comparative study and analyzed 2181 TSPs performed on 1862 patients. A significant difference was found between the complication rates related to TSP of groups undergoing TSP with and without ICE (0.9% vs. 3.1%, p 0.001).…”
Section: Transseptal Puncturementioning
confidence: 99%